The Danubian States Concern over the Solution of Cases with Minors: Array - Giurgea, Lenuta; Ion, Carmen (Journal of Danubian Studies and Research, 2021)
Throughout the time, the growing number of international couples has led to the appearance of an impressive amount of litigation involving minors, which also represent the most difficult legal issues. In order to solve them, the Member States make every effort to align with the relevant legislation. Managing such an international process is a great challenge for legal specialists. At European level, this challenge is exacerbated by both the high standards and the guarantees provided to the parties in both international and Community civil proceedings. In the past, children's rights were not completely approached in the European Union. The only legislative framework was the regulation of large-scale economic and political issues affecting children. At present, there is a macro level concern about children projection, including the protection of all their rights and freedoms. There is an ongoing important role in the cases concerning minors within the European Court of Justice. Until recently, the Court had resolved only a few such cases. As new, much clearer legislative measures have been adopted regarding the children's rights, the cases resolved by the court have skyrocketed. Many of these decisions refer to children's rights in terms of free movement.